(untitled) (Tydskrif vir Christelike Wetenskap | Journal for Christian Scholarship, 2006)
The first part of the article concerns the theological doctrine of creation, which is not to be confused with the theory of creationism. The doctrine of creation is that there is only one unoriginated being, God, on whom all else depends for existence. Since this doctrine is chiefly associated with the first two chapters of Genesis, I start by examining them. My purpose is to arrive at a proper understanding of them relative to their place in the canon and their own internal structure. My conclusion is that when read properly, i.e., as covenant, the text neither yields scientific information nor needs to be reconciled to science. But this conclusion is not then hitched to the hasty inference that science and religion have nothing to do with one another. On the contrary, in the second part I argue that no theory can avoid being regulated by some divinity belief or other, so that there are no religiously neutral theories.